The Telecommunication Sector in the Palestinian Territories : A Missed Opportunity for Economic Development - World Bank Group (World Bank, Washington, DC, 2016)
The Telecommunications Sector Assessment Note in the Palestinian territories is a knowledge product prepared by the World Bank in response to a specific request from the Palestinian Ministry of Telecommunications and Information Technology (MTIT) to assess the performance of the telecommunications sector, identify specific issues and make recommendations for further development and reform.